Performance Evaluation of VoIP in MPLS network using NS-2 - Chaudhary, Dr. Anu; Singh, Dr. Satya Prakash (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
To evaluate and enhance the performance of the High-Speed Data networks some study on network technology is required to be done, it also require to simulate and verify the results and suggests the better solutions for High-Speed Data networks like Real-time Data network (Multimedia data, Voice data). Multiprotocol Label Switching (MPLS) is an emerging technology and plays an important role in the next generation networks by providing Quality of service (QoS). It overcomes the limitations like excessive delays and high packet loss of IP networks by providing scalability and congestion control. The key feature of MPLS is its Traffic Engineering (TE) which is used for effectively measuring the performance of the networks and efficient utilization of network resources. MPLS provides lower network delay, efficient forwarding mechanism, scalability and predictable performance of the services which makes it more suitable for implementing real-time applications such as Voice and video. In this paper performance of Voice over Internet Protocol (VoIP) application is implemented in MPLS network and conventional Internet Protocol (IP) network. NS-2 (Network Simulater-2) is used to simulate the both networks and the comparison is made based on the metrics such as Voice packet delay, voice packet lost probability, throughput, voice packet send and received. The simulation results are analyzed and it shows that MPLS based solution provides better performance in implementing the VoIP application. The simulated results in the form of animations and graphs can be helpful for network operators or designers to determine the number of VoIP calls, to estimate the packet lose probability and other QoS parameters that can be estimated and evaluated for a given network by using NS-2 simulator.